'Who decided this?': Negotiating epistemic and deontic authority in systemic family therapy training. (February 2022) - Nanouri, Katerina; Tseliou, Eleftheria; Abakoumkin, Georgios; Bozatzis, Nikos
In this article we illustrate how trainers and trainees negotiate epistemic and deontic authority within systemic family therapy training. Adult education principles and postmodern imperatives have challenged trainers' and trainees' asymmetries regarding knowledge (epistemics) and power (deontics), normatively implicated by the institutional training setting. Up-to-date, we lack insight into how trainers and trainees negotiate epistemic and deontic rights in naturally occurring dialog within training. Drawing from discursive psychology and conversation analysis, we present an analysis of eight transcribed, videotaped training seminars from a systemic family therapy training program, featuring three trainers and eleven trainees. Our analysis highlights the dilemmatic ways in which participants resist and affirm the normatively implicated trainers' deontic and epistemic authority. Trainers are shown as mitigating directives and trainees as resisting them, with both displaying (not)knowing, while attending to concerns about (a)symmetry. We discuss our findings' implications for systemic family therapy training.